“Standard Assessment Framework”: A Proposal to Fill a Gap in the “Paris Declaration” - Hellmut W. Eggers; Daniel Svoboda (Journal of MultiDisciplinary Evaluation)
Background: The “Paris Declaration” (PD), is a statement by which, in 2005, leading representatives/actors of International Development Cooperation agreed on a series of ways and means with a view to improving aid effectiveness. Among those ways and means, the need for the establishment, by partner countries, of national “Assessment Frameworks” was stressed without, however, alluding to the nature and content of such frameworks. This must be considered a serious gap.